2016
DOI: 10.1186/s40337-016-0127-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for elevated liver enzymes during refeeding of severely malnourished patients with eating disorders: a retrospective cohort study

Abstract: BackgroundThere are few previous reports regarding the cause and evolution of liver injury in patients with anorexia nervosa (AN) during the refeeding process, and its management remains controversial. This study aimed to determine the risk factors for elevated liver enzymes during refeeding and their effect on the therapeutic process in severely malnourished patients with eating disorders.MethodsIn a retrospective cohort study of 167 female inpatients in a single hospital from January 2004 to March 2015, 67 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
14
1
1
Order By: Relevance
“…Medical complications should be reported consistently across future studies to assist with interpretation. Along with those complications reported in the studies conducted by Zuercher et al 24 and Matthews et al, 25 other studies also recommend monitoring alanine aminotransferase 40 and prealbumin levels 41 during refeeding. The effects of different refeeding approaches on long‐term outcomes, such as relapse and psychological distress, also remains unclear 29 …”
Section: Discussionmentioning
confidence: 97%
“…Medical complications should be reported consistently across future studies to assist with interpretation. Along with those complications reported in the studies conducted by Zuercher et al 24 and Matthews et al, 25 other studies also recommend monitoring alanine aminotransferase 40 and prealbumin levels 41 during refeeding. The effects of different refeeding approaches on long‐term outcomes, such as relapse and psychological distress, also remains unclear 29 …”
Section: Discussionmentioning
confidence: 97%
“…Indeed, individuals with mild-to-moderate anorexia nervosa, who are predominantly younger women, were likely to have been enrolled in the study. However, because many studies have shown that both serum AST and ALT activities are high in patients with anorexia nervosa [15,16], it is possible that, in fact, few individuals with anorexia nervosa were enrolled in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with a serum AST of ≥200 IU/L, an ALT of ≥200 IU/L, and/or a gamma glutamyl transpeptidase (GGT) of ≥300 IU/L were excluded. Subjects with a BMI of <13 kg/m 2 were also excluded because this is the mean BMI for Japanese inpatients with anorexia nervosa [15,16]. Furthermore, subjects with a BMI of ≥40 kg/m 2 were excluded because this is the threshold for class III obesity, which is very rare in the Japanese population (0.02%–0.07%) [13,17].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, physicians must provide complete care considering the refeeding syndrome in severely malnourished patients and restrict the initial calorie intake. 16 Refeeding syndrome is defined as the metabolic alternations that develop due to rapid nutritional repletion in chronically malnourished patients. 15 17 With attentive monitoring via ECG, anthropometry, head CT and blood tests, we were able to avoid fatal medical complications.…”
Section: Discussionmentioning
confidence: 99%